Strategies addressing orientation and mobility challenges facing students with visual impairment in selected Tanzanian universities - Mwitango Shemndolwa; Kenneth Kapalu Muzata; Magdalene Simalalo (Eureka: Journal of Educational Research, 2025)
The increased number of students with Visual impairment (VI) in universities has been noticeable in recent years. The growing population faces multiple challenges regarding orientation and mobility (O&M). This study explores the strategies to address the challenges encountered in O&M by university students with VI in Tanzania. An intrinsic case study design was employed to generate in-depth information on the challenges and strategies used to overcome the obstacles faced in the orientation and mobility for students with visual impairment. Eighteen students with VI, three orientation and mobility specialists and four administrators were purposively selected to participate in the study. Data were collected through interviews, focus group discussions and observation to ensure data triangulation. Inductive thematic analysis was used to make sense of the data generated from two selected universities. The findings revealed a variety of challenges, including internal and external challenges such as unsupportive infrastructure, extreme fear and an absence of clear landmarks in the university environments. The strategies employed to overcome these challenges included self-development, resilience, as well as awareness and adaptability to the environment. Based on the findings, it is recommended that universities continue to build and modify infrastructure while considering the inclusivity of students with VI to facilitate effective use of O&M skills, allowing for confident and independent movement within the universities.